Effect of Maize Husk Treatment of Crude Oil Contaminated Soil on Morphological and Biochemical Indices of Cowpea Seedlings - O. Aruoren; P. Onakurhefe; O. B. Onyeukwu; O. A. Ohwokevwo; F. I. Achuba (Journal of Applied Sciences and Environmental Management, 2022)
The ameliorative potential of maize husk on crude oil impacted soil had been documented. The aim of this study was to evaluate the effect of maize husk treatment of crude oil contaminated soil on morphological and biochemical indices of cowpea seedlings. Treatment of soil with maize husk significantly (p< 0.05) increased the morphological and biochemical indices comparable to control seedlings. On the other hand, exposure of cowpea seedlings to crude oil-contaminated soil caused significant (p< 0.05) decreases in both morphological and biochemical indices compare to values in control seedlings. However, these values were restored close to control values   by treatment of crude oil-contaminated with maize husk. The treatment of soil with maize husk caused improvement of morphological parameters and alteration of biochemical indices of cowpea seedlings grown in uncontaminated and crude oil-contaminated soils. This has affirmed the use of maize husk as possible soil conditioner.